2021
DOI: 10.1016/s1473-3099(20)30764-7
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evidence for reinfection with SARS-CoV-2: a case study

Abstract: Background The degree of protective immunity conferred by infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is currently unknown. As such, the possibility of reinfection with SARS-CoV-2 is not well understood. We describe an investigation of two instances of SARS-CoV-2 infection in the same individual.Methods A 25-year-old man who was a resident of Washoe County in the US state of Nevada presented to health authorities on two occasions with symptoms of viral infection, once at a commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
741
9
25

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 726 publications
(826 citation statements)
references
References 28 publications
27
741
9
25
Order By: Relevance
“…Indeed, it has been reported that a patient reinfected with SARS-CoV-2 had more severe COVID-19 than the initial infection. 33 Without any other rational explanations, the results support our hypothesis that immunity to type S virus underlies the exacerbation of COVID-19 in Europe. 5 Serosurveys in Kenya have suggested that the epidemic in Africa was like that in the West; 34 however, in contrast to the West, most patients were asymptomatic or mildly ill. On the African continent, in contrast to Europe, many of the epidemics were due to Clade S. Our previous analysis suggested that the outbreak of type K virus after type S offsets the effect of type S to increase CFR.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, it has been reported that a patient reinfected with SARS-CoV-2 had more severe COVID-19 than the initial infection. 33 Without any other rational explanations, the results support our hypothesis that immunity to type S virus underlies the exacerbation of COVID-19 in Europe. 5 Serosurveys in Kenya have suggested that the epidemic in Africa was like that in the West; 34 however, in contrast to the West, most patients were asymptomatic or mildly ill. On the African continent, in contrast to Europe, many of the epidemics were due to Clade S. Our previous analysis suggested that the outbreak of type K virus after type S offsets the effect of type S to increase CFR.…”
Section: Discussionsupporting
confidence: 78%
“…As discussed above, although a majority of COVID-19 patients developed one or more antigen-specific antibodies to SARS-CoV-2, the rapid decline of antibodies in most of the convalescent COVID-19 patients and the weak antibody responses in asymptomatic and mild cases as well as immunosuppressed patients suggest that SARS-CoV-2 reinfection may be more common than currently appreciated. Numerous case reports have been published on COVID-19 reinfection Lee et al, 2020a;Li et al, 2020a;McGrath et al, 2020;Prado-Vivar et al, 2020;Sanyaolu et al, 2020;Selvaraj et al, 2020;Tillett et al, 2020;Torres et al, 2020). One report showed that three patients free of viral load but having low levels of anti-S and N-specific antibodies were re-infected (Li et al, 2020a).…”
Section: Are Recovered Covid-19 Patients Protected From Reinfection?mentioning
confidence: 99%
“…Finally, the medical staffs working in the front line have not been infected till date, which effectively prevented secondary infections and spread of the disease in the hospital (11). Re-infection cases were reported in Hong Kong and the United States (12,13). Based on the known literatures and our research, we believe that patient immunity is helpful to avoid infection, but not all patients can produce immunity after infection.…”
Section: Discussionmentioning
confidence: 74%